Turkish Ministry of National Education school-based disaster education program: A preliminary results of the program evaluation. (January 2021) - Gokmenoglu, Tuba; Sonmez, Elif Dasci; Yavuz, Ibrahim; Gok, Abdulcelil
Abstract: The Turkish Republic of Ministry of National Education carries out a project, namely the School-Based Disaster Education, to increase the positive attitudes towards preparedness, provide basic knowledge on disaster risk reduction, and increase teachers' practical skills. The training program comprises three elements; distance training program, face-to-face teacher trainer program, and local teacher training program. The 567 trainer teachers and 135, 375 local teachers were trained by the cascade training system. The qualities of the program were evaluated by using Stufflebeam's Context, Input, Process, Product evaluation model. Findings showed that the program made remarkable changes at knowledge, attitude, and behavioral levels. Some recommendations are discussed due to the teachers' report on the obstacles in reaching the program outcomes. Highlights: SBDE improves preparation skills. Blended learning approach is found useful. DRR programs should consider needs of learners.